2014
DOI: 10.1155/2014/436821
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Case of Malignant Pleuropericardial Effusion: HHV-8-Unrelated PEL-Like Lymphoma—A Case Report and Review of the Literature

Abstract: Primary effusion lymphoma (PEL) or body cavity lymphoma is a rare type of extra nodal lymphoma of B-cell origin that presents as lymphomatous effusion(s) without any nodal enlargement or tumor masses. It belongs to the group of AIDS related non-Hodgkin's lymphomas. First described in 1996 in HIV infected individuals who were coinfected with Kaposi's sarcoma-associated herpesvirus (KSHV) or HHV-8 virus, it was included as a separate entity in WHO classification of tumors of hematopoietic and lymphoid tissue in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…Using this simple criterion based on HHV8 association, we reviewed the literature cases and separated the previously reported and our current cases (total cases: 256) as either classical (type 1) PEL or type II PEL (or EBL). 6,7,12,16,19,22,[24][25][26][27]38 As listed in Tables 3 and 4, the ratio of type I to type II PEL was 2:1. Compared to type II PEL, type I PEL was associated more frequently with HIV and EBV infection (both P < 0.001), while MYC rearrangement was less frequent than type II PEL (3% versus 29%; P = 0.004; Table 5).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Using this simple criterion based on HHV8 association, we reviewed the literature cases and separated the previously reported and our current cases (total cases: 256) as either classical (type 1) PEL or type II PEL (or EBL). 6,7,12,16,19,22,[24][25][26][27]38 As listed in Tables 3 and 4, the ratio of type I to type II PEL was 2:1. Compared to type II PEL, type I PEL was associated more frequently with HIV and EBV infection (both P < 0.001), while MYC rearrangement was less frequent than type II PEL (3% versus 29%; P = 0.004; Table 5).…”
Section: Discussionmentioning
confidence: 94%
“…In the literature, the terms ‘PEL’ and ‘EBL’ are somewhat confusing in use, and sometimes these names seem to have been used interchangeably. Some HHV8‐negative cases have been reported as PEL . As the term ‘primary effusion lymphoma’ is self‐explanatory and is easy to understand, while the term ‘effusion‐based lymphoma’ is a little obscure and is not readily distinct from PEL, we propose to call the HHV8‐positive cases ‘classical’ or ‘type I PEL’ and the HHV8‐negative cases ‘type II PEL’, stressing the similarities between these two groups, although there is an immunophenotypical difference.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To date, few papers have investigated the clinical features and the treatment of PEL‐LL patients who are generally elderly, express CD20 for pan‐B‐cell antigens, and have a slow prognosis for mortality 5, 6. PEL has a strong prognosis for mortality during the early phase, whereas the literature includes numerous reports of favorable responses to chemotherapy in patients with PEL‐LL 7.…”
Section: Discussionmentioning
confidence: 99%
“…Those cases are considered a rare disease entity called HHV8-unrelated PEL-like lymphoma [3] . Advanced age [4] remains the only known risk factor for PEL-like lymphoma, and the pathogenic mechanisms remain unclear. It has been reported that patients with HHV8-unrelated PEL-like lymphoma show better outcomes than patients with PEL [5] .…”
Section: Discussionmentioning
confidence: 99%